Love and Desire in Coetzee’s Disgrace and Waiting for the Barbarians: A Levinasian Approach - Teimouri, Mahdi (SARE: Southeast Asian Review of English, 2019)
This paper explores the possibility of presenting a philosophical analysis of two novels, Waiting for the Barbarians and Disgrace, by J. M. Coetzee, through a Levinasian ethical perspective. Levinas’s philosophy is premised on the ethical responsibility of the self for the other. Redefining philosophy as the wisdom of love, Levinas embarks upon a revisionary approach to re-defining concepts such as love, desire, and responsibility that dominate and mediate the relationship between the self and the other. These reconfigured terms accommodate Levinas’s distinctive ethical standpoint, one that is geared towards valorizing the other over the self. The novels examined in this article similarly manifest a tendency to prioritize the other in its destitution and vulnerability. My discussion of Waiting for the Barbarians will be built around the relationship between the Magistrate and the Barbarian girl. I contend that their non-carnal relationship can be interpreted in terms of a transcendental and nonontological conception of desire. As such, desire becomes an obsession which cannot be shaken off. Desire of this kind liberates the self from egoism. In Disgrace I will explore the concept of love as maternity. Lucy’s refusal to abort her pregnancy reverberates with Levinas’s argument about maternal love as a self-effacing form of devotion. In both novels the question of the ethical body and its vulnerability will also be examined. The aim is to show how insatiable desire and maternal love can be manifestations of the ethical responsibility expounded by Levinas